STRATEGI CONTENT MARKETING UNTUK MENINGKATKAN BRAND RECOGNITION UMKM KULINER STUDI KASUS PADA NASI TELOR MA EDJA BANDUNG - Ravitilova, Ravitilova; Afiany, Fitri Dewi; Audria, Hazkia Rifany (Politeknik Negeri Ambon, 2025)
Introduction: Culinary micro, small, and medium enterprises (MSMEs) often encounter major obstacles in establishing brand recognition, especially within highly competitive digital ecosystems. Nasi Telor Ma Edja, a home-based culinary venture in Bandung, exemplifies these challenges. The growing dominance of social media as a marketing tool necessitates strategic and adaptive approaches. This study aims to improve brand recognition for Nasi Telor Ma Edja by applying a content-driven digital marketing strategy on Instagram, a platform that has proven effective for micro-brands seeking greater exposure and audience engagement. Methods: This study adopted a case study approach conducted over a three-month campaign period. The strategic framework focused on aligning Instagram content with the brand’s core identity. Key activities included scheduled visual content posting, the use of unique promotional copywriting, consistent visual branding, and the deployment of paid advertising features. The campaign's effectiveness was evaluated through social media analytics, including follower growth, account reach, impressions, and engagement rate metrics. Results: The implementation of the content marketing strategy led to substantial improvements in all key performance indicators. Follower counts increased, the brand's content reached a wider audience, and both impressions and engagement rate demonstrated consistent upward trends. Notably, the engagement rate exceeded industry benchmarks for micro Instagram accounts. These outcomes highlight the effectiveness of targeted, consistent content strategies in building brand recall and fostering digital consumer engagement, especially within the MSME sector